2012
DOI: 10.1111/j.1467-9221.2012.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Value Differentiation Between Enemies and Allies: Value Projection in National Images

Abstract: The current study aimed to investigate value projection between Palestinians, Israelis, Americans, and Swiss as a function of their group's stance toward the Israeli‐Palestinian conflict. Drawing on image theory, we assumed that images—operationalized by value projection—would be a function not just of features of the target group, but of the rater group's relationship with the target group. Value projection can be seen as an indicator of (de)humanization as values represent goals and desirable behaviors of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…This view fits with image theory, proposing that perceptions of the values and goals of out-groups influence alliance and enemy formation as people and leaders demonize or dehumanize those they deem to have threatening or incompatible values (Alexander, Brewer, and Hermann 1999; Healy et al 2002). Eicher, Pratto, and Wilhelm (2013) found that Israelis, Palestinians, Americans, and the Swiss assigned values opposite from what they hold more to their enemies than their allies. The notion of self-as-values anchored in identity (Hitlin 2003) also finds support in recent research emphasizing that individuals seek goal-directed action verifying their moral identities (Stets and Carter 2012), with moral priorities shaping individual action (Miles 2015).…”
Section: Values and Social Identitiesmentioning
confidence: 91%
“…This view fits with image theory, proposing that perceptions of the values and goals of out-groups influence alliance and enemy formation as people and leaders demonize or dehumanize those they deem to have threatening or incompatible values (Alexander, Brewer, and Hermann 1999; Healy et al 2002). Eicher, Pratto, and Wilhelm (2013) found that Israelis, Palestinians, Americans, and the Swiss assigned values opposite from what they hold more to their enemies than their allies. The notion of self-as-values anchored in identity (Hitlin 2003) also finds support in recent research emphasizing that individuals seek goal-directed action verifying their moral identities (Stets and Carter 2012), with moral priorities shaping individual action (Miles 2015).…”
Section: Values and Social Identitiesmentioning
confidence: 91%
“…Another set of studies suggested that accuracy in value perceptions depends on the attributes of the perceiver (Feather & Cross, 1975) and the perceived (Knafo & Schwartz, 2003). Finally, value PARTNER'S PERCEIVED VALUES 6 perceptions may reflect, in part, a projection of own values (Eicher et al, 2013;Lee et al, 2009).…”
Section: Perceived Values and Behaviormentioning
confidence: 99%
“…More recent empirical research also suggests that different national images are related to different sets of emotions and action tendencies (Brewer & Alexander, ), that the strength of one's social identity and social dominance orientation differentially shape the endorsement of national images (Alexander, Levin, & Henry, ), and that we are more likely to project our values onto allies than enemies (Eicher, Pratto, & Wilhelm, ). Furthermore, Alexander, Brewer, and Livingston () have used the image framework to better understand intergroup relations outside the international context, exploring, for instance, interethnic relations (see also Bilali, ; Bilali, Celik, & Ok, 2014; Özkececi‐Taner, ).…”
Section: International Image Theorymentioning
confidence: 99%